A Hybrid Architecture Framework for Simulations in a Service‐Oriented Environment. Issue 3 (6th July 2017) - Hannay, Jo Erskine; Brathen, Karsten; Mevassvik, Ole Martin
ABSTRACT: Service orientation, and more recently, the notions of cloud technology that service orientation enable, are designed to accommodate the need for flexible enterprise business processes. Through standardized interfaces, a service‐oriented architecture (SOA) should enable one to build and rebuild software systems readily and rapidly in a methodological manner. However, certain domains have specialized architectural standards; an example in point is modeling and simulation (M&S), for which there exist mature architectural standards, that may even have many of the characteristics strived for in SOA. An important issue is, therefore, how to integrate specialized architectures into a wider SOA. Using defense information systems and M&S as a case, we outline a hybrid architecture framework for specialized architectures in an encompassing SOA. Although it may be possible to dissolve a specialized architecture into the encompassing SOA at implementation time, we argue that it is important to be able to model the specialized architecture as an integral intact part. We further advocate a pragmatic notion of reference architecture in terms of appropriate level of abstraction and domain specificity to avoid pitfalls that may render architecture work unusable.